Model Survei Cerdas Lalu Lintas Harian Rata-Rata (ADT) untuk Perencanaan dan Pemantauan Perkerasan - Arthur Daniel Limantara; Tjahjaning Tingastuti Surjosuseno; Bambang Subiyanto; Fauzie Nursandah; Hery Lilik Sudarmanto; Sri Wiwoho Mudjanarko (CAHAYAtech, 2020)
Survey volume of daily traffic for the planning and supervision of pavement road manually requires effort, time and cost is not cheap. Besides that, accuracy, and speed in getting the data are not timely, especially as real-time data. This study aims to get an intelligent survey model that will function to get daily traffic volume data automatically and in real-time, as well as its processing. The methodology used is to model the survey process by utilizing smart devices, microcontrollers, sensors, and the internet of things, as well as cloud and client-server programming. The survey process model can be divided into two parts, namely part one whose task is to collect vehicle data and part two to collect the axle load of each vehicle, then the data will be sent through an access point to the cloud, cloud data is taken from the access point at the data processing center on the server computer to done processing. The model generating information volume data traffic at speeds up to 67.4 Mbps, to accurately the data 98%, and the real-time and the results of data processing can be used as surveillance of pavement age.